2020
DOI: 10.1016/j.desal.2020.114335
|View full text |Cite
|
Sign up to set email alerts
|

Transport and structural properties of osmotic membranes in high-salinity desalination using cascading osmotically mediated reverse osmosis

Abstract: Management of high-salinity brines is a global environmental challenge. Recently, we proposed a novel cascading osmotically mediated reverse osmosis (COMRO) technology for energy-efficient hypersaline desalination. In this study, a transport model is established for COMRO. We investigate the impacts of hydraulic pressure and salinity on transport and structural properties of thin-film composite osmotic membranes in COMRO. Our results show that transport properties are not affected by transitory pressure change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…30 TSSE desalination is not restricted by feedwater salinity, unlike membrane-based reverse osmosis (RO) with hydraulic pressure (or, equivalently, osmotic pressure) limitation. 20,35,36 Because TSSE desalination does not require a phase change of water, the high energetic penalty of the vaporization enthalpy is inventively sidestepped and significantly higher energy efficiencies are attainable, specifically for hypersaline brines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…30 TSSE desalination is not restricted by feedwater salinity, unlike membrane-based reverse osmosis (RO) with hydraulic pressure (or, equivalently, osmotic pressure) limitation. 20,35,36 Because TSSE desalination does not require a phase change of water, the high energetic penalty of the vaporization enthalpy is inventively sidestepped and significantly higher energy efficiencies are attainable, specifically for hypersaline brines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The RO test is not convenient to properly estimate the real A and B intrinsic parameters of FO membranes. [ 38,43,44 ] In RO, the applied pressure tends to compact the membrane which then alters the effective surface membrane. Unlike both active and support layers, any change in the active‐support interlayer structure may modify the A, B values and the overall membrane mass transport.…”
Section: Database and Comparison Criteria Of The Manufacturing Techniquesmentioning
confidence: 99%
“…Unlike both active and support layers, any change in the active‐support interlayer structure may modify the A, B values and the overall membrane mass transport. [ 43 ] Chen et al [ 43 ] have shown that the active‐support interlayer is a crucial element. They also showed that the BA ratio of TFC membranes does not vary with changes in the interlayer morphology.…”
Section: Database and Comparison Criteria Of The Manufacturing Techniquesmentioning
confidence: 99%
See 2 more Smart Citations